Some remarks from A. A. Berger - Arthur Asa Berger (Connectist Istanbul University Journal of Communication Sciences)
This issue of Media, Communication and Conflict appears at a time when conflicts have become more and more common and terrible. After many years of peace in Europe, thanks to a decision made by one man it would seem, Vladimir Putin, Russia invaded Ukraine and a terrible war has broken out which involves, directly and indirectly, many other countries namely with some countries supporting Russia and many supporting Ukraine. And in November, Hamas terrorists invaded Israel and killed 1400 people there and took more than 200 hostages back to Gaza. In return, Israel has declared war on Hamas and has attacked Gaza with terrible consequences for Gaza and Israel.